Detection of hydrocarbon level in distilled water using laser induced acoustic techniques - Sarbalaei, Raheleh Hosseinian (2015)
Oil spill occurs almost every day. Department of chemistry Malaysia (JKM) took almost a week or more days to analyze it. Therefore alternative technique should be considered. In this work, a new technique is introduced by using laser technology and piezoelectric transducer. The system is known as Laser Induced Acoustic (LIA). Lube oil was used as a hydrocarbon sample. Distilled water and hydrochloric acid were employed for solution preparation with different concentrations in the range of 0 - 1000 ppm. Hydrocarbon became impurities in the solution, which can be observed via CCD video camera after illumination by diode pumped solid-state laser (DPSS). Refractive index of hydrocarbon solution was measured by He-Ne laser following Snell‘s law. A Q-switched Nd:YAG laser was focused to induce optical breakdown and shock wave generation. This phenomenon was recorded via high-speed photography system. Dye laser pumped by nitrogen laser was employed as a source of flashlight. Digital delay generator was deployed to synchronize both lasers. CDD camera was interfaced with personnel computer with Matrox version 9 software, which was used to record shock wave. Silicone photodiodes were employed to detect both lasers. Optical delay between two lights represented the frozen time of shock wave generation. The time delay was manifested via digital oscilloscope. Shock wave propagation in hydrocarbon solution was also detected via piezoelectric transducer. The sound signal was also displayed on the same oscilloscope. The sound amplitude (volt) was calibrated via hydrometer to estimate shock wave pressure (atm). Shadowgraph image of shock wave was analyzed via ImageJ software. Shock wave radius was measured and divided by optical delay to determine sound speed in hydrocarbon solution at different concentration. Observation result showed that sound speed linearly increases with hydrocarbon concentrations. Similarly sound amplitude was found linearly increasing with hydrocarbon concentrations. This is due to a lot of mass transfer which gives rise to high impact to the transducer. Combination of high-speed photography and transducer detection validate the shock wave as the mechanism to determine the hydrocarbon concentration. Hence sound speed is the fingerprint for every hydrocarbon solution. Furthermore sound speed has linear relationship with hydrocarbon concentration. Similarly the sound amplitude has linear relationship with hydrocarbon concentration. This similarity indicates that the hydrocarbon concentration can be detected based on sound generation via laser induced acoustic technique.